The altitude factor and its effect on the variation in rainfall amounts (Bani Walid - Gharyan as a model): The altitude factor and its effect on the variation in rainfall amounts (Bani Walid - Gharyan as a model) (jornal of the libyan geographical society, 2021)
The study aims to reveal the variation in rainfall amounts in the Bani Walid and Gharyan regions, as the amount of rainfall varies from place to place, and it is rare to find two places that are completely similar in their climatic conditions. If they are similar in temperature, for example, you will find that they differ in the amount of rain that falls on them or in its distribution throughout the year.While similar in temperature and rainfall, they differ in prevailing wind direction. The research addressed the importance of altitude in increasing rainfall rates in the Gharyan region, where the annual average rainfall is approximately 349.4 mm, located at an altitude of 741 meters. In Bani Walid, the annual average rainfall is 58.5 mm.Located at an altitude of 259 meters, the study concluded that rainfall amounts for the Nafas gradually decrease as the effort south of the Gharyan region increases until we reach less than 100 mm in most years. The study recommended the need to pay attention to establishing meteorological stations that cover all areas in the study region to obtain climate data.And to work on taking measures to reduce the negative effects of the water problem.
Keywords: Climate; Rainfall rates; Monthly rain rates; Annual rainfall rates